Counter-Community as Moral Community: The Church’s Contribution to Public Civility - Bismoko Mahamboro, Dionius (MELINTAS An International Journal of Philosophy and Religion (MIJPR), 2018)
Indonesia is a home of various religions and traditional beliefs. However, from the time before the fall of the New Order in 1998 up to now the coexistence of followers of different religions cannot be said to be without problems. The 2004 Indonesian Bishops’ Conference’s pastoral notes reflect the worry that the peaceful coexistence among different religious followers is failing. Nevertheless, the document’s dominant node is expressed in positive attitude and hope. The Indonesian Bishops’ Conference encourages all Christian communities to develop themselves into ‘counter-communities’. This article is aimed at discovering the relevance of the idea ‘counter-communities’ to the problems of coexistence of different religious followers in the Post-New-Order era, which now has been marked with prejudice and mistrust.